Synthesis and Characterization of Zirconia-Silica PMMA Nanocomposite for Endodontic Implants - Puji Widodo; Wawan Mulyawan; Nina Djustiana; I. Made Joni (MDPI AG, 2023)
This study aimed to enhance the mechanical properties of PMMA composites by introducing various types of fillers, including ZrO2, SiO2, and a mixture of ZrO2-SiO2 nanoparticles, which were prepared as prototypes for an endodontic implant. The ZrO2, SiO2, and mixed ZrO2-SiO2 nanoparticles were synthesized using the sol-gel method and the precursors Tetraethyl Orthosilicate, Zirconium Oxychloride, and a mixture of both precursors, respectively. Before polymerization, the as-synthesized powders were subjected to the bead milling process to obtain a well-dispersed suspension. Two scenarios for the fillers were implemented in the preparation of the PMMA composite: a mixture of ZrO2/SiO2 and ZrO2-SiO2 mixed with two different types of silane: (3-Mercaptopropyl) trimethoxysilane (MPTS) and 3-(Trimethoxysilyl) Propyl Methacrylate (TMSPMA). The observation of the characteristics of all of the investigated fillers included the use of a particle-size analyzer (PSA), a Zeta-potential analyzer, FTIR, XRF, XRD, and SEM. The mechanical properties of the MMA composites, as prepared under various scenarios, were observed in terms of their flexural strength, diametrical tensile strength (DTS), and modulus of elasticity (ME). These levels of performance were compared with a PMMA-only polymer. Each sample was measured five times for flexural strength, DTS, and ME. The results showed that the best PMMA composite was SiO2/ZrO2/TMSPMA, as revealed by measurements of the flexural strength, DTS, and ME corresponding to 152.7 ± 13.0 MPa, 51.2 ± 0.6 MPa, and 9272.8 ± 2481.4 MPa, which are close to the mechanical properties of dentin. The viability of these PMMA composites, as measured up to day 7, was 93.61%, indicating that they are nontoxic biomaterials. Therefore, it was concluded that the PMMA composite created with SiO2/ZrO2/TMSPMA can be considered to be an acceptable endodontic implant.